Occurrence of the Parasitic Copepod Ergasilus labracis on Threespine Sticklebacks from the South Coast of Newfoundland. Issue 4 (16th October 2014) - Eaves, Alexandra A.; Ang, Keng Pee; Murray, Harry M.
Abstract: A study conducted from August to October 2013 surveyed Threespine Sticklebacks Gasterosteus aculeatus ( n = 822) for the presence of parasitic copepods in the vicinity of large sea‐cage salmonid farms in Bay d'Espoir, Newfoundland. The majority of parasitic copepods surveyed were Ergasilus labracis ( n = 4, 684). Other parasitic copepods observed on Threespine Sticklebacks during the survey included chalimus‐stage Lepeophtheirus spp. ( n = 3), adult Argulus alosae ( n = 2), and a single Thersitina gasterostei . This represents a new host record for E. labracis . The copepods were present on fish collected in a broad range of temperatures (6.9–17.7°C) and salinities (10.2–30.2 [Practical Salinity Scale]). The parasitic copepods were most commonly found on larger hosts estimated to be age 1 or older. Surprisingly, the highest infestations (approximately 65%) were found on regions of the hosts outside of the gills (behind the pectoral fins and pelvic spines); in some cases, the copepods had inflicted significant damage to the skin of their hosts. Among host fish with evidence of an additional infection, such as microsporidian tumors (xenomas) or hemorrhagic‐like symptoms (dark red abdomens and bloody mucus), the prevalence of E. labracis was significantly higher (43.4%) than among healthy fish (28.9%) despite there being no significant difference in size between the two fish health groups. In contrast, intensity (mean number of individual parasites per host) was significantly higher among healthy hosts (23.6) than among unhealthy ones (7.63). Although this parasite has been listed as present in Newfoundland previously, it has a broad host range and has been reported to be pathogenic to farmed salmonids. Therefore, its potential impact on wild and farmed fish populations around Newfoundland should not be underestimated. Received March 28, 2014; accepted June 16, 2014